2020
DOI: 10.1038/s41598-020-73337-0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct phenolic, alkaloid and antioxidant profile in betel quids from four regions of Indonesia

Abstract: Betel quid (BQ) is a chewing mixed package that mainly contains areca nut (AN), betel leaf (Leaf) or betel stem inflorescence (SI), and slaked lime, and is consumed with or without tobacco BQ chewing is common in South East Asia and has been strongly associated with malignant and potentially malignant diseases of the oral cavity. Alkaloids such as arecoline are often accounted for the carcinogenic potential of BQ, however the chemical composition of BQ has not been studied in detail. In the current study, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…There are different groups of identified compounds, and most of them belong to terpenes and higher fatty acids. Arecolin, a typical compound in areca nuts [25,26], has also been identified.…”
Section: Qualitative and Semiquantitative Analysis Of Areca Nutsmentioning
confidence: 99%
“…There are different groups of identified compounds, and most of them belong to terpenes and higher fatty acids. Arecolin, a typical compound in areca nuts [25,26], has also been identified.…”
Section: Qualitative and Semiquantitative Analysis Of Areca Nutsmentioning
confidence: 99%
“…Arecoline concentration also varies geographically. In our recent study investigating the chemical composition of Indonesian BQ mixtures [8], the highest arecoline concentration was observed in the nuts and BQ mixtures from West Papua; BQ mixtures from other regions of the country showed a considerable reduction of arecoline concentration.…”
Section: Alkaloid: Arecolinementioning
confidence: 89%
“…Areca nut, also known as betel nut, is the seed of the areca palm (Areca catechu) tree, typically grown in tropical regions. Alkaloids are one of the many well-known chemical compounds associated with areca nut [8], but other major chemical constituents have been known for decades and include crude fibre, proteins, lipids, carbohydrates, tannins, flavonoids and minerals [9]. Importantly, the concentration of each chemical constituent varies between the raw and ripe nut.…”
Section: Why It Is Important To Understand the Effects Of Individual ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sazwi et al, for instance, showed that slaked lime impaired cytoprotective and anti-oxidant activities of betel nut [22]. To further analyze different components of betel nuts, Sari et al [23] conducted a study to investigate the characteristics of betel nuts and their relationship to oral malignancy. Their results showed that slaked lime increased pH value.…”
Section: Discussionmentioning
confidence: 99%